Shaping Medan : The Role and Impact of Prominent Chinese 1890-1942 - Buiskool, Dirk Aedsge (Asian Studies E-Books Online, Collection 2025, 2025)
The City of Medan on Sumatra emerged from the large-scale plantation industry. The plantations were characterized by harsh labor conditions, and frequently described as an area of suppression and struggle. In contrast, the city of Medan itself maintained a relatively harmonious atmosphere. A significant factor contributing to this harmony was the influence of nine Chinese businessmen. This book, featuring previously unpublished archival materials and interviews, explores the contributions of these prominent Chinese figures to Medan's economic, social, healthcare, and politics..